PERENCANAAN PARTISIPATORI DALAM MEMBUAT PROGRAM DAN PENGAMBILAN KEPUTUSAN PENDIDIKAN - Ninik Hidayati; Akhmad Zaini (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2017)
In the field of education, the planning process is one of the key factors in the effectiveness of the implementation of education activities to achieve the expected educational objectives for each level and type of education at the national, as well as local level. However, when viewed in reality everyday, elements of the process of education planning is still more used as a complement or elaboration of policy leaders, so often the goal set is not achieved optimally. One of the reasons is that educational planners still lack understanding of planning processes and mechanisms in a more comprehensive context. In addition, the position of the planning field is not a "key factor" of the existence of an educational institution, both at the macro and micro level, so that the contribution of education planning to the achievement of vision, mission, and educational goals has not been felt optimally.